Sosialisasi Marketing Digital Menuju Era Society 5.0 di SMA Negeri 1 Belimbing Kabupaten Muara Enim - Agus Mulyani; Edduar Hendry; Yasir Arafat; Ilhamsyah Ilhamsyah; Akila Akila; Heryati Heryati; Tri Darmawati; Aprizal Rosadian (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The era of Society 5.0 demands the integration of digital technology into various aspects of life, including the field of education. This study aims to describe the digital marketing strategies implemented by SMA Negeri 1 Belimbing in Muara Enim Regency in facing the challenges and opportunities of the Society 5.0 era. Using a qualitative descriptive approach, data were collected through observations, interviews, and documentation with the school’s stakeholders, as well as content analysis of the school's official social media platforms.The research findings show that SMA Negeri 1 Belimbing has utilized various digital platforms such as Instagram, Facebook, and the school’s website to strengthen its institutional image, establish communication with the community, and increase the school's appeal to prospective students. The use of digital marketing also supports digital transformation within the school environment through innovative and adaptive approaches to contemporary developments.The conclusion of this study emphasizes the importance of schools being prepared to integrate digital technology as part of their institutional marketing strategy in the transition toward the Society 5.0 era.